The expression of ppars gamma in the cervical cancer line, bela and the effects of specific PPAR ligand on cell growth - Yaacob, Nik Soriani (Pusat Pengajian Sains Perubatan, 2013)
To quantify the mRNA expression levels of PPARy in the cervical cancer cell line, HeLa, using real-time PCR. To correlate the findings in (1) with the corresponding protein expression levels by Western blotting. To correlate the transcriptional and translational levels of PPARy with markers of apoptosis in these cells. To determine whether addition of specific PPARy ligands to the tumour cell line would modulate the above parameters.